2001
DOI: 10.1016/s0004-9514(14)60272-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of weightbearing in the clinical assessment of knee joint position sense

Abstract: Knee joint position sense was assessed by active tests with active limb matching responses in supine lying and in unilateral weightbearing (WB) stance using (re)positioning of the whole limb whilst focusing on the knee, and in supine lying using (re)positioning confined to the knee. Following five tests at approximately 45 degrees knee flexion in all three test conditions, position sense was found to be significantly more accurate and reliable following the WB procedure. Possible explanations are, first, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 26 publications
5
62
0
2
Order By: Relevance
“…The results of the current study are similar to those reported by Ghiasi and Akbari [23] , Stillman and McMeeken [24] , Hyouk…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study are similar to those reported by Ghiasi and Akbari [23] , Stillman and McMeeken [24] , Hyouk…”
Section: Discussionsupporting
confidence: 92%
“…Active ipsilateral matching is a commonly used and accepted method for measuring JPS [20,32]. It has face validity because muscle receptors are the primary contributors to proprioceptive information.…”
Section: Ptrrticipuntsmentioning
confidence: 99%
“…Knee JPS was examined using ipsilateral active matching under both non-weightbearing (NWB) and single leg weightbearing (We) test conditions [2,32]. The NWB position confines JPS testing to the knee joint while the WB position is more functional.…”
Section: Ptrrticipuntsmentioning
confidence: 99%
“…Knee JPS was examined under non-weightbearing and uni-and bilateral weightbearing test conditions using validated and reliable protocols [33]. Four reflective markers were fixed with double-sided adhesive tape to the skin of the lateral thigh and leg over the apex of the greater trochanter, iliotibial tract level with the posterior crease of the 80"-flexed knee, neck of the fibula and prominence of the lateral malleolus.…”
Section: Procedurrsmentioning
confidence: 99%